#SocialMedia: Exploring the Relationship of Social Networking Sites on Body Image, Self-Esteem, and Eating Disorders. (May 2017) - Santarossa, Sara; Woodruff, Sarah J.
The aim of this study was to investigate whether problematic social networking site (SNS) use (i.e., degree of dependent relationship with SNSs), total SNS time/day, total SNS friends, and specific SNS activities were related to body image (BI), self-esteem (SE), and eating disorder (ED) symptoms/concerns. A sample of young adults ( N  = 147) completed an online survey which measured SNS usage, problematic SNS use, BI, SE, and ED symptom/concerns. The findings revealed that females and males spent 4.1 ± 3.9 and 2.9 ± 2.8 hr on SNS, respectively, with the majority of time spent lurking (i.e., looking at another users' profile but not actually communicating with them). Furthermore, problematic SNS use was found to be related to BI, SE, and ED symptoms/concerns. Moreover, SNS activities, such as lurking and posting comments on others' profiles, were found to be related to BI, whereas SNS total time was found to be related to ED symptoms/concerns. Overall, this study demonstrates the possible correlational influence of SNSs on BI, SE, and ED symptoms/concerns.